PENYULUHAN KESEHATAN MENJAGA ANAK SEHAT DAN BAHAGIA DI MASA PANDEMI COVID-19 - Nindya Aryanty; Attiya Istarini; Ima Maria; Susan Tarawifa; Adelina Fitri (Universitas Jambi, 2021)
ABSTRACT The COVID-19 pandemic has had an impact on learning methods, namely from face-to-face to distance learning. Digital devices can provide highly sophisticated learning opportunities for early childhood. However, in conditions of activity restrictions during the pandemic, people have a tendency to use digital devices as a means of education, entertainment, and social interaction, which means that they also increase the duration of screen time in their daily lives. According to the American Academy of Child and Adolescent Psychiatry (AACAP), the maximum screen time for toddlers is 1 hour per day. Excessive screen time in children has been shown to be associated with behavioral health problems. The level of parental knowledge regarding the allowed screen time duration is quite good. This can be seen from the survey results where, after giving the material, respondents who have children in the 3-5 year age group who know the screen time duration is less than 1 hour are around 84.7% of respondents, where before receiving the material only 63.4% of respondents . Meanwhile, for respondents who have children aged 6-12 years as much as 77.1% know screen time after getting the material, where previously only 63.9%. It can be concluded that the implementation of this counseling was able to increase the knowledge of parents about the impact of excessive use of gadgets so as to prevent the adverse effects of gadgets such as negative behavior, obesity, and internet or gadget addiction. In addition, it is necessary to conduct counseling on the adverse effects of using gadgets in the adolescent and adult age groups. Keywords: COVID-19, Child Health, Screen Time ABSTRAK Pandemi COVID-19 memiliki dampak pada metode pembelajaran yaitu dari tatap muka menjadi pembelajaran jarak jauh. Perangkat digital dapat memberikan peluang belajar yang sangat canggih bagi anak usia dini. Namun dalam kondisi pembatasan aktivitas selama pandemi, masyarakat memiliki kecenderungan untuk menggunakan perangkat digital sebagai sarana pendidikan, hiburan, dan interaksi sosial, yang artinya turut meningkatkan durasi screen time dalam keseharian. Menurut American Academy of Child and Adolescent Psychiatry (AACAP), durasi screen time pada balita maksimal 1 jam per hari. Durasi screen time yang berlebihan pada anak-anak telah diketahui memiliki asosiasi terhadap permasalahan perilaku kesehatan. Tingkat pengetahuan orang tua mengenai durasi screen time yang diperbolehkan sudah cukup baik. Ini terlihat dari hasil survey dimana, setelah pemberian materi, pada responden yang memiliki anak di kelompok usia 3-5 tahun yang mengetahui durasi screen time kurang dari 1 jam adalah sekitar 84,7% responden, dimana sebelum mendapat materi hanya 63,4% responden. Sedangkan untuk responden yang memiliki anak usia 6-12 tahun sebanyak 77,1% mengetahui screen time setelah mendapatkan materi, dimana sebelumnya hanya 63,9%. Dapat disimpulkan pelaksanaan penyuluhan ini ternyata dapat meningkatkan pengetahuan para orang tua mengenai dampak penggunaan gadget berlebihan sehingga mencegah terjadinya efek buruk gadget seperti perilaku negatif, obesitas, dan kecanduan internet atau gadget. Selain itu perlu dilakukan penyuluhan dampak buruk penggunaan gadget pada kelompok usia remaja dan dewasa. Kata Kunci: COVID-19, Kesehatan Anak, Screen Time